PENGARUH PEMBELAJARAN IPS DENGAN MEDIA TEKNOLOGI INFORMASI KOMUNIKASI DAN KOMPETENSI GURU TERHADAP MINAT BELAJAR SISWA MTSN DI KABUPATEN TAPIN - Sitti Maryam (Universitas Lambung Mangkurat, 2015)
This research aims to find out the Influence of Social Science Subject with Information Technology and Communication and Teacher’s competence toward Learning Interest of MTsN Students in Tapin Regency. This research is survey; the subject of research is all students of MTsN of ninth grade for academic year 2013/2014 di Tapin Regency and this is called total sampling. This is quantitative approach. The data collection uses quesionaire and documentation. The test validity is based product moment correlation. The research result states that there is the correlation between information technology and communication based social science learning and students interest in learning; there is the correlation between teacher’s competence and student’s interest; there is the correlation among information technology based social science learning and teacher’s competence toward communication toward student’s interest in learning. In a word, technology and communication based social science learning influences student’s interest; teacher’s competence influences student’s interest; information technology based social science learning and teacher’s competence influence student’s interest in learning. It is recomended that this research can be the study relevant to develop the social science teachers’ concept contextually. Key words: Social Science Subject, Teacher, and Learning Interest